FORMS OF LAW IMPLEMENTATION AND THEIR SPECIFIC FEATURES: AN EMPIRICAL SOCIO-LEGAL ANALYSIS (World Bulletin of Management and Law, 2026)
The practical realization of legal norms manifests in four forms: observance, execution, utilization, and enforcement. This empirical socio-legal study evaluates how different demographic groups engage with these forms by analyzing 450 participants (300 general citizens and 150 legal professionals) using a standardized assessment tool. The results reveal a significant societal dichotomy. The general populace predominantly relies on passive 'Observance' and state-driven 'Enforcement' (68% reliance in civil disputes), indicating a critical deficit in independent legal utilization. Conversely, legal professionals demonstrate significantly higher engagement in the active 'Utilization' and 'Execution' of their rights (78.4 ± 5.2 vs. 45.2 ± 4.5, p < 0.001). The study concludes that transitioning from a passive legal culture to an autonomous, rights-based civil society requires targeted educational interventions to enhance public capacity for active legal utilization, thereby reducing the administrative burden on state enforcement agencies.